Selection of Forklift Unit for Warehouse Operation by Applying Multi-Criteria Analysis - Atanasković, Predrag; Gajić, Vladeta; Dadić, Ivan; Nikoličić, Svetlana (Promet - Traffic&Transportation, 2025)
This paper presents research related to the choice of the criteria that can be used to perform an optimal selection of the forklift unit for warehouse operation. The analysis has been done with the aim of exploring the requirements and defining relevant criteria that are important when investment decision is made for forklift procurement, and based on the conducted research by applying multi-criteria analysis, to determine the appropriate parameters and their relative weights that form the input data and database for selection of the optimal handling unit. This paper presents an example of choosing the optimal forklift based on the selected criteria for the purpose of making the relevant investment decision.